2018
DOI: 10.1002/ijc.31532
|View full text |Cite
|
Sign up to set email alerts
|

Colony stimulating factor 1 receptor blockade improves the efficacy of chemotherapy against human neuroblastoma in the absence of T lymphocytes

Abstract: Tumor-associated macrophages can promote growth of cancers. In neuroblastoma, tumor-associated macrophages have greater frequency in metastatic versus loco-regional tumors, and higher expression of genes associated with macrophages helps to predict poor prognosis in the 60% of high-risk patients who have MYCN-non-amplified disease. The contribution of cytotoxic T-lymphocytes to anti-neuroblastoma immune responses may be limited by low MHC class I expression and low exonic mutation frequency. Therefore, we mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…No studies have monitored immune markers in the TME during chemotherapy in patients. An in vivo mouse study showed that depletion of TAMs from NBL tumors is associated with increased chemotherapeutic efficacy without requiring T cell contribution [56]. This observation led to the author's suggestion to combine CSF-1R blockade with chemotherapy to potentially increase treatment efficacy.…”
Section: Chemotherapymentioning
confidence: 99%
“…No studies have monitored immune markers in the TME during chemotherapy in patients. An in vivo mouse study showed that depletion of TAMs from NBL tumors is associated with increased chemotherapeutic efficacy without requiring T cell contribution [56]. This observation led to the author's suggestion to combine CSF-1R blockade with chemotherapy to potentially increase treatment efficacy.…”
Section: Chemotherapymentioning
confidence: 99%
“…Detailed analysis of the Csf1r mutant phenotypes could therefore contribute to the identification of specific and universal features of organism-wide macrophage development. In addition, it is important to understand the systemic effects of CSF1R inhibition on macrophages, as inhibition of CSF1R is a clinical strategy for the intentional depletion of macrophages in various disease contexts, including Alzheimer’s disease, brain injury and cancer (Edwards et al, 2019; Lloyd et al, 2019; Tap et al, 2015; Webb et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of dysregulation of CSF1‐CSF1R (a.k.a. macrophage colony‐stimulating factor receptor, the product of the c‐fms protooncogene) signaling has inspired the clinical use of receptor‐tyrosine kinase inhibition to treat tenosynovial giant cell tumors, and prompted clinical trials of selective CSF1 and CSF1‐receptor inhibitors that have shown promising activity as a targeted therapy for this disease (eg, NCT01643850, http://clinicaltrials.gov), as well as in other tumors that over‐express CSF1 …”
Section: Introductionmentioning
confidence: 99%
“…gov), [9][10][11][12] as well as in other tumors that over-express CSF1. 13 While the most common CSF1 fusion partner has been reported to be COL6A3, identified in 33% of cases, and thought to result in overexpression of full-length CSF1 via promoter swapping, 7 others have reported that the CSF1 breakpoint was downstream of exon 5, and led to the replacement (by alternate sequences) of the 3 0 untranslated region (UTR) in an otherwise intact CSF1. [14][15][16] Thus, it has been proposed that truncation of this region may account for CSF1 overexpression in some cases of tenosynovial giant cell tumor.…”
mentioning
confidence: 99%